(untitled) (Applied Biological Research, 2020)
The study evaluates the immunomodulatory effect of vitamin E against the side effect of synthetic food dye-induced oxidative damage and nephrotoxicity in male mice. Mice were divided into 4 groups viz., group 1 as control mice, group 2 received vitamin E (100 mg kg-1 bw), group 3 administered with carmoisine (250 mg kg-1 bw), and group 4 received carmoisine and vitamin E for 28 days. Nephrotoxicity induce in mice was assessed by observing the changes in levels of renal markers, and antioxidant status. Administration of vitamin E significantly restored the levels of renal functions (urea and creatinine), antioxidants status and immunological parameters (TNF-a, Cox-2, Bcl-2, CD95 and caspase 3). The prophylactic role of vitamin E against food dye-induced toxicity may be attributed to their antioxidant effects and free radical scavenging properties.